2017
DOI: 10.5937/psistra1701009d
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual foundations of inclusive systems in and around schools for early school leaving prevention: An emotional-relational focus

Abstract: Against the background of the EU2020 headline target of reducing early school leaving to 10% across Europe, this article examines the conceptual foundations of the understanding of inclusive systems for early school leaving prevention that has emerged in EU policy documents and research reports in recent years. Traditionally, inclusive education has referred to a focus on children with special educational needs. However, this conceptual review examines how inclusion is increasingly being examined in broader te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Accordingly, their decision to ignore ‘official’ application paths and seek work through social networks and recruitment agencies can be seen as a form of stigmatization management (Goffman, 1963, 1986; see also Gesthuizen et al, 2011; Làmont and Lareau, 2015; Solga, 2002). Early school leavers need access to high-quality education and career guidance, psychological and emotional support (see Downes et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, their decision to ignore ‘official’ application paths and seek work through social networks and recruitment agencies can be seen as a form of stigmatization management (Goffman, 1963, 1986; see also Gesthuizen et al, 2011; Làmont and Lareau, 2015; Solga, 2002). Early school leavers need access to high-quality education and career guidance, psychological and emotional support (see Downes et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Voss et al, 1966), a situation that has been rectified by more recent research (e.g. Downes et al, 2017; Lessard et al, 2008). Most studies and typologies on early school leaving concentrate on its causes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Downes, Nairz-Wirth, and Rusinaitė (2017) [ 40 ] have indicated that multi-level policies focusing on the integration of individuals at their school should be incorporated as imperative methods of action. These policies should involve the following: (1) The generation of organizational and curricular strategies targeting the classroom climate, (2) the running of activities to strengthen relationships that incentivize social participation in all groups, (3) teacher training on diversity and improving the classroom climate, and (4) the development of interprofessional networks where teachers, together with other professionals, can pose doubts and difficulties in the pursuit of deepening understanding.…”
Section: Discussionmentioning
confidence: 99%
“…According to Smith et al (2004) [ 42 ], in contexts where the educational center or school can provide meeting points to promote interaction between pupils and favor the generation of new and diverse friendships, all of those implicated will become aware of diversity aspects. Downes, Nairz-Wirth, and Rusinaitė (2017) [ 40 ] have explained that involving families and converting the school into a social hub will result in a reduced prevalence of bullying as the entire educational community will be more involved and aligned towards achieving the objective of combatting school bullying.…”
Section: Discussionmentioning
confidence: 99%
“…School (including the heritage language school) and home continued to operate as “two solitudes” (Cummins, 2008; Li & Lin, 2022). There is a need to reconceptualize and operationalize schools and families as one connected system, each having a set of relationships and mutual influences that impact the children (Downes et al, 2017). This requires the schools and parents to work together to remove some of the systemic obstacles, such as language and cultural differences, and to create relational spaces within the schools to work reciprocally with culturally and linguistically diverse children and families (Li, 2008).…”
Section: What Lessons Did We Learn For Multiliteracies Education Beyo...mentioning
confidence: 99%